Construções políticas das concepções ambientais/climáticas na Argentina: mudanças e continuidades - Braga, Patricia Benedita Aparecida (Universidade Federal de São Carlos, 2019)
Argentina sanctified the UNFCCC in 1993 and accomplished its differentiated obligations, the creation of the National Comunications (mapping of causes and possible solutions for climate changes in a national scale). Thus, the present work has the general goal of understanding the historical and contextual meaning attributed by the Argentinian State to the climate changes, by the tracing of ideational and contextual changes. In specific terms, there are four purposes: to understand Argentina's participation in the genesis of the global environmental debate; to analyse the country's possible pioneerism in the South America region in the way of handling the environment issue; to highlight how the idea of environment has changed throughout the years (from primordial element of possible economical and political transformation to a instrumentalized unit by the principle of economical gain and loss); and, description and processual analysis of institutional and ideational aspects and agents involved in the construction of the climate and environmental issues by the Argentinian State. As an analytical guide the discursive institutionalism and its dialogue with other institutionalisms (rational choice, historical and sociological) was operationalized by the selection of works by Argentinian intellectuals who worked with this theme. In methodological terms, the process tracing, the documental analysis and semistructured interviews conducted the analysis. In general terms, it is concluded that the Argentinian State was the exponent in the genesis of the debate on the global environmental issue and in the handling of this issue as a political problem, besides being the pioneer regarding the ideational conception of environment as a central changer of the international economical reality (Péron). And, that the conceptions about climate changes in current times goes beyond the relative capacity of the country of changing the causes of the problem and the ideational understanding of the "State", by his agents (of several natures) of understanding the gains and losses of acting in the face of the phenomenon, clearly shown by directions and discreet changes, whether in national terms or international ones.
Political constructions regarding environmental/climate issues in Argentina: changes and continuities of ideas, actors and institutions
Keywords: Estado; Ambiente/mudanças climáticas; Instituições; Atores; Ideias; State; Environment/climate change; Institutions; Actors; Ideas; CIENCIAS HUMANAS::CIENCIA POLITICA